2008
DOI: 10.7888/juoeh.30.235
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Simultaneous Analytical Method of Urinary Nicotine and Its Metabolites, and Their Half-Lives in Urine

Abstract: The objectives of this research were to improve and standardize a relatively easy, highly sensitive and highly accurate method of measuring nicotine, cotinine and trans-3'-hydroxycotinine in the urine of non-smokers exposed to environmental tobacco smoke (ETS) and to clarify the reliability of this method. Blinded studies using this analytical method were conducted in two universities. Standard solutions of nicotine, cotinine and trans-3'-hydroxycotinine were prepared at one university, divided in two parts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the US alone, nearly 88 million nonsmokers ages 3 and older live in homes where they are exposed to sufficient levels of SHS+THS to produce significant blood levels of cotinine (a metabolite of nicotine) and tobacco-specific nitrosamine, carcinogens that result from the reaction of nicotine with nitrous acid in the environment [ 3 ]. These metabolites have been found to be present in the urine of infants and children living in the homes of smokers [ 4 – 6 ]. In a separate study, an association was found between on-set of insulin resistance and type 2 diabetes in adolescents that grew up in households where at least one parent smoked cigarettes [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the US alone, nearly 88 million nonsmokers ages 3 and older live in homes where they are exposed to sufficient levels of SHS+THS to produce significant blood levels of cotinine (a metabolite of nicotine) and tobacco-specific nitrosamine, carcinogens that result from the reaction of nicotine with nitrous acid in the environment [ 3 ]. These metabolites have been found to be present in the urine of infants and children living in the homes of smokers [ 4 – 6 ]. In a separate study, an association was found between on-set of insulin resistance and type 2 diabetes in adolescents that grew up in households where at least one parent smoked cigarettes [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use nitrosamines to compare between humans and mice because the half-life of the nitrosamines (days) is much longer than that of cotinine (hours) and therefore makes the comparison between our well-controlled experiments and not-as-well-controlled human data collection more reliable [27], [28]. The intermittent exposure of children to cigarette smoke introduces uncertainty in cotinine data because the timing between the exposure and the urine collection for a study cannot be closely controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Only 8.1% of the 160 children submitting urine for analysis had detectable cotinine (≄0.5 ng/mL). Although cotinine is the primary metabolite of nicotine, it has a half-life of 16 to 30 hours 23,24 and likely has limited sensitivity in the setting of intermittent exposure.…”
Section: Discussionmentioning
confidence: 99%